1997
DOI: 10.1161/01.hyp.29.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Differential Human Renal Tubular Responses to Dopamine Type 1 Receptor Stimulation Are Determined by Blood Pressure Status

Abstract: We performed the present studies to determine whether a proximal renal tubular dopamine D1-like receptor defect exists in human essential hypertension. Twenty-four subjects were studied (13 normotensive and 11 hypertensive) in a randomized, double-blind, vehicle-controlled study using fenoldopam, a selective D1-like receptor agonist. Subjects were studied in sodium metabolic balance at 300 mEq/d, after which the salt sensitivity of their blood pressure was determined. Fenoldopam at peak doses of 0.1 to 0.2 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
84
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 24 publications
3
84
0
2
Order By: Relevance
“…Thus, the ability of fenoldopam to decrease renal vascular resistance is maintained in the spontaneously hypertensive rat (SHR) (41). Fenoldopam increases effective renal plasma flow to a greater extent in salt-sensitive hypertensive than in normotensive subjects (15). The ability of dopamine to relax renal artery strips is also increased in stroke-prone SHRs (42).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the ability of fenoldopam to decrease renal vascular resistance is maintained in the spontaneously hypertensive rat (SHR) (41). Fenoldopam increases effective renal plasma flow to a greater extent in salt-sensitive hypertensive than in normotensive subjects (15). The ability of dopamine to relax renal artery strips is also increased in stroke-prone SHRs (42).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, disruption of the D 1 receptor in mice produces hypertension (12, 13). The pivotal role of dopamine in the excretion of sodium after increased sodium intake has led to the hypothesis that an aberrant renal dopaminergic system is important in the pathogenesis of some forms of genetic hypertension (3,5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Several mechanisms potentially responsible for the failure of endogenous renal dopamine to engender a natriuretic effect in genetic hypertension have been investigated and ruled out, including decreased renal dopamine production and receptor expression, aberrant nephron segment distribution of dopamine receptors, defective effector enzymes (adenylyl cyclase or phospholipase C), and abnormal renal sodium transporters (3,8,13,17).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…23 It has been shown that the absence of DA codifying alleles is related to increases in systolic and diastolic pressure, thus suggesting a causal relation between the gene for the D 1A receptor and AHT. 24,25 Also, defects of coupling or activation of second messengers by this receptor (without affecting their distribution or quantity) are also related to the AHT appearance. 21 In this regard, the presence of polymorphic forms of the D 1 codifying gene has been described in patients with essential AHT.…”
Section: Role Of Dopamine In Kidney Functionmentioning
confidence: 99%